Open quantum systems an introduction - Rivas, Angel; Huelga, Susana F. (New York Springer, 2012)
(3z(BThe book is a monograph dealing with a selection of topics in open quantum systems theory. Its particular aim with respect to other publications is to connect the results to a more solid mathematical background so that most results are directly proven, even though proofs are usually restricted to a finite-dimensional setting to keep matters simple. $1! = (BThe monograph is written in a clear and concise style and provides a compact introduction to the subject $1! = (B.(3ys
Keywords: Quantum theory; Open systems (Physics); Mathematical physics